Real earnings management, CEO experience, family ownership, and external audits: A meta-analysis - Nowicki, Mikołaj (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2024)
This article analyses the relationship between real earnings management (REM) and corporate governance variables, including family ownership, external audit quality, and CEO experience. The studies analysed were published between 2006 and 2021. The Sarbanes-Oxley Act of 2002 and the implementation of international financial reporting standards have led companies to reduce the use of accrual earnings management (AEM), and instead adopt real earnings management. However, many authors claim that using REM might harm a company’s long-term wellbeing, which accentuates the need to study the determinants of REM. The variables analysed in this paper are extensively covered in the literature, however, there is still ambiguity regarding their relationship with REM due to conflicting findings; some studies indicate a positive relationship, while others show a negative one. To resolve this ambiguity, meta-regression analysis is employed. The results indicate a positive relationship between family ownership and REM. This highlights the need to explore other forms of ownership to determine the most effective ownership structure that does not increase REM. This is of interest to legislators. The results provide no evidence to support the statistical or economic significance of CEO experience and external audit in relation to REM.